Horizontal structure of the rare plant populations and elementary methods of its analysis (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The scheme of placing plants in the population are the basis for the horizontal structure analysis. The shown schemes illustrate the horizontal structure of Sempervivum globifera, Pulsatilla pratensis, Jovibarba globifera and Huperzia selago populations based on the conducted studies in 2007-2014 years. The intracenotic mosaic of the habitats was estimated. The influence of the phytocenotic mosaic elements and microrelief specifics on the plants inside their populations were analyzed. Such data enabled to understand more deeply some ecological characteristic of the studied sites. Moreover, it was shown that the vertical profiles of the trees stand in the area of 5×50 m or more are the most appropriate to illustrate ecotonic locations in the linear populations as the edges. In the studied sites with Jovibarba globifera, Pulsatilla pratensis and Sempervivum ruthenicum the ecological discomfort ratio were evaluated that defined the confinement of these species to the certain type of tree stands relief and density. As a result of studying shrub-herbaceous and moss -lichen layers composition and structure was shown the reason of uneven plants placing in the populations. On the examples of Jovibarba globifera and Huperzia selago plants were defined the confinement of the individuals to those or other elements of the horizontal phytocoenoses structure. The most commonly J. globifera plants were found on the bedding and shown that it mostly avoided areas where the mosses are dominating. In case of H. selago plants, the dynamics of interaction with mosses over 6 years were also analyzed. It was shown that new H. selago plants appear in such points where the mosses curtain thickness is not exceed 3–5 cm high. The young plants are often withered in places where the moss layer is higher than 4 cm. Adult H. selago plants are able to grow successfully at the height of the moss cover above 5–6 cm beyond the domination of Dicranum polysetum and Pleurozium schreberi.
Keywords: mapping plant populations, Sempervivum ruthenicum, Pulsatilla pratensis, Jovibarba globifera, Huperzia selago.